The Student Parties at Ramkhamhaeng University: Case Study of Tawanmai Student Party - Inkaew, Kitchaiyakul (Legal State Journal, 2023)
This research article aims to study the origin, development and management of the Tawanmai Student Party. Qualitative in-depth interviews were conducted with 5 key informants. The results showed that Tawanmai Student Party originated from a conflict between the Phithak-Tham Student Party and its supporters who disagreed with the party’s management. Therefore, they resigned from the Phitak-Tham Party and started a new party: the Tawanmai Student Party. The Tawanmai Student Party assumed its strength in three stages. The first stage was between 1992 and 2002. In the first 5 years (1992-1997) problems encountered with the failure in the election to the Ramkhamhaeng University Student Union. It was caused by a lack of financial support from external sponsorship and the candidates were unknown to the students of Ramkhamhaeng University. After this experience the Tawanmai Student Party get a strong external sponsorship. This led to the victory of election and it had been winning continuously 4 terms between 1998 and 2001. The second stage was between 2003 and 2013. This stage was prosperous. The Tawanmai Student Party had learned from the past and changed its way of dealing with the public. They focused on the “media” such as organizing a popular concert according to the trend in the university. This led to win the election of 2005 and 5 following elections between 2008 and 2012. The third stage was between 2014 and 2013. It is the declining stage. At that stage of development the Tawanmai Student Party could not win the election for 6 years (2008 – 2019). It was until the period 2020 – 2023 that the Tawanmai Student Party could come back and won the election for 4 successive years. This was due to the fact that the party could keep the promises with the allied parties and adapt the concept “New Thinking and New Action” to gather the mass depending on the circumstances at the time. Concerning the party management, the Tawanmai Student Party will concentrate on the participation of every member. There are also “Seniors” who always advise and coordinate the party’s internal and external work outside the university campus.